Learning Management at Pondok Senyum Indonesia: Analysis of Planning, Implementation, and Evaluation - Alhamidi, Teguh Iqbal; Muharam, Moch. Panji; Jabar, Padli Abdul; Mahmud (Jurnal Manajemen Pendidikan, 2024)
Background The implementation of learning in schools has become increasingly innovative, making management play a crucial role in the development of learning. Purpose The purpose of this study is to understand how learning development management is conducted at Pondok Senyum through an analysis of management dimensions: planning, actuating, and evaluation. Design/method/approach This research employs a qualitative method, utilizing data collection techniques such as observation and interviews, and analyzed using descriptive analysis techniques. Results The findings reveal that the learning development management at Pondok Senyum has been implemented well, starting from planning formulation derived from its vision, as well as the implementation process. However, the evaluation dimension needs improvement. It is hoped that by optimizing all dimensions of management, effective and efficient learning management can be achieved. Therefore, the evaluation dimension should become a primary focus moving forward in learning development management. Contribution/value The planning and implementation that have been carried out cannot measure their effectiveness. This should become a main focus for Pondok Senyum in the future, as in learning management, it is not enough to simply formulate good planning, and it is not enough to execute the plan effectively in the actuating stage.